Cultural influences on choosing green products: An empirical study in Malaysia - Ihwan, G.; Salwa Hanim, A.R.; Siti Zawiah, M.D.; Hideki, A.; Alva Edy, T.; Novita, S. (Impact Factor, 2017)
Over the past few years, there have been increasing efforts to promote green products in developing nations. However, evaluating customer preferences when it comes to choosing green products is a rather complex task, which is perhaps due to the influence of cultural values on customer preferences. Hence, the objective of this study is to examine the influence of cultural value dimensions on customer preferences for green products in Malaysia. The sample consists of 615 Malaysian citizens and the data were analysed using the structural modelling approach. Based on the results, there are three cultural value dimensions that have a significant influence on customer preferences for green products in Malaysia: (1) uncertainty avoidance, (2) long-term orientation and (3) power distance. The implications of this study and recommendations for public policy and business orientation are also discussed in this paper in order to accelerate the attainment of sustainable development.